STEM-03. NOVEL METASTATIC BRAIN TUMOR TARGETS ISOLATED THROUGH PHAGE DISPLAY BIOPANNING AGAINST BRAIN METASTASIS-INITIATING CELLS. (5th November 2018) - Kim, Jongmyung; Bao, Shideng; N. Rich, Jeremy; Liu, James
Abstract: Despite treatment advances for primary cancers that may result in brain metastases, the treatment for brain metastases has lagged behind, partly due to the unique environment created by the central nervous system. Recent work has highlighted that metastatic brain tumors demonstrate significant genotypic deviation from their parental tumors, which highlights the need to focus on metastatic brain tumors for the development of more effective targeted therapeutics. The epithelial-mesenchymal transition suggests the existence of brain metastasis-initiating cells (BMICs), which may possess stem cell-like phenotypes that play a pivotal role in metastasis. To properly isolate this subpopulation of tumor cells, we compared patient derived metastatic brain tumor cells against brain metastasis cell lines. We found that both types of cells demonstrated similar morphology when grown in standard serum media conditions, but when grown in serum-free media, both demonstrated a tumor sphere morphology. Gene expression analysis showed increased expression of stem cell markers CD133 and EYA1 when grown in serum-free media. To isolate therapeutic targets specific to BMICs, we performed in vitro and in vivo phage display biopanning against BMICs. Analysis of the recovered peptides derived several potential targets. Among them were angiomotin (AMOT) and bromodomain testis-specific factor (BRDT). Gene expression analysis confirmed significant upregulation of these gene in metastatic brain tumors cells when compared to non-tumor neural cells and primary lung cancer cell lines. Tissue microarray analysis of eleven matched brain metastasis and primary lung cancer patient tissue from Moffitt Cancer Center demonstrated an increased expression in brain metastasis over primary lung tissue. Analysis through NIH GEO database demonstrated decreased survival with increased gene expression. Our results show that we can use phage display biopanning to isolate novel targets that may be specific to metastatic brain tumors by isolating the proper growth conditions that support the BMIC phenotype.